Strategi Pengembangan Usaha Suwar Suwir “Abi” di Desa Panti Kecamatan Panti Kabupaten Jember (Studi kasus : Di Desa Panti Kecmatan Panti Kabupaten Jember) - Nisa, Khoirun; Pudjiastutik, Endang Wahyu (Program Studi Agribisnis, 2021)
ABSTRACT Indonesia is an agricultural country that has abundant natural resources in the form of agricultural products. The food crops sub-sector is one of the agricultural products that has an important role as a supplier of consumption needs. The aims of the research were (1) to know the 4p marketing mix/marketing mix of the “abi” suwar suwir business in Panti Village, Panti District, Jember Regency. (2) To find out the development strategy in the